A finite element assessment of chip formation mechanisms in the machining of CFRP laminates with different fibre orientations. (15th July 2021) - Cepero-Mejías, F.; Phadnis, V.A.; Kerrigan, K.; Curiel-Sosa, J.L.
Abstract: The virtual assessment of a composite machining process using finite element (FE) models constitutes a cost-effective solution to study the surface quality of machined parts. Thus, the correct simulation of the chip fracture becomes essential to obtain consistent numerical results. This work develops an original FE approach to emulate the chip formation in the machining of carbon fibre reinforced polymer (CFRP) laminates. Composite damage initiation modes are evaluated via hybrid Puck-Hashin composite failure criteria. Subsequently, mechanical properties of the damaged elements are linearly degraded. Finally, a novel strain-based element deletion criterion is applied to reliably simulate the chip release process. Five different cutting configurations are successfully modelled. The influence of relevant fibre orientations and cutter rake angles on chip formation are analysed in detail. The shape of the simulated chips reaches a high similarity with the chips obtained in relevant experimental trials presented in the literature. Useful insights about the modelling of sub-surface damage in composite machining are also produced in this investigation. For instance, the modelling of the fibre bending damage which take place in the machining of 90° laminates is modelled with great precision.